Effects of sludge application on the initial growth of Eucalyptus citriodora Hook - Freier, Matias; Malavasi, Ubirajara Contro; Malavasi, Marlene de Matos (Revista de Ciências Agroveterinárias, 2006)
This study compared the effects of increasing sludge rates on the early growth of E. citriodora Hook. The experiment used plastic pots (5 L. volume). Sludge rates equivalent to 0, 3, 6, 12 and 24 t ha-1 were incorporated into the soil or applied at the soils surface. Growth variables were measured 100 and 203 days after planting. The sludge application method affected the seedling initial growth. Dosages equivalent to 12 and 24 t ha-1 promoted higher seedling height when applied at the soil surface than when they were incorporated to the soil. There was no significant effect of the sludge rates on the seedling stem diameter at both evaluation times. Sludge application at the soil surface promoted higher root collar diameter (4.39 mm) than sludge incorporation to the soil (3.86 mm).